Acute and chronic ocular outcomes in SJS/TEN patients treated with oral ciclosporin vs intravenous immunoglobulin - Foo, Valencia Hui Xian; Yueh, Lee Haur; Mehta, Jodhbir S.; Ong, Hon Shing (Frontiers in Medicine, 2024)
Background/Aim: To evaluate differences in ocular complications of Stevens Johnson Syndrome (SJS)/Toxic Epidermal Necrolysis (TEN) patients receiving either systemic IVIG or Ciclosporin (CsA) as initial treatments. Methods: Retrospective review of consecutive patients admitted for SJS/TEN at the Singapore General Hospital (SGH) from 2011 to 2017 who received either IVIG or Ciclosporin at the onset of the disease and had ophthalmological follow-up of at least 6 months were included. Acute ocular severity of SJS/TEN was graded using the Gregory grading score; chronic ocular complications were graded using the Sotozono system. Results: A total of 18 subjects were included for analysis, with 8 in the IVIG group and 10 in the CsA group. There were no significant differences in acute Gregory severity grading between the 2 groups. The CsA group had a trend toward worse overall chronic Sotozono grading scores compared to the IVIG group (median [IQR]: 2 [0 – 3] vs 1 [0 – 6.5], p=0.27), with a higher incidence of acute severe cornea involvement (60% vs 25%, p=0.93) and chronic corneal and eyelid involvement in the former than the latter. SJS/TEN patients with worse acute ocular involvement were more likely to have TEN and perianal mucosal involvement. (50% vs 0, p=0.01). Conclusion: Compared to those who received IVIG, SJS/TEN patients who received CsA at the acute disease stage, seemed to have worse acute corneal and chronic corneal and eyelid complications. Larger studies are needed to confirm this finding.